The Role of Self-Practice Midwife on Maternal Health Services for The Period of The Covid-19 Pandemic in Palu City - Mantao, Elvaria; Larasati, Rahma Dwi; Marselina (Media Publikasi Cendekia Indonesia, 2022)
The objective of this study was to know the relationship among the role of self-practice midwife on maternal health services based on the Antenatal Care variable, contraception method, and maternity services on Covid-19 pandemic period in Palu city. This study used cross sectional design method. The population on this study was all self-practice midwifes in Palu city as much as 57 and the sample was 56. The research variables consist of the characteristics of the respondents (age, education), The Role of Independent Practice Midwives (serve, not serve), Antenatal Care (Good, Not Good), Contraceptive (Good, Not Good), Maternity Mother ((Good, Not Good). This study was used Chi-square test with the number of significance was p<0,05. The result of this study showed that there was relation between self-practice midwife on ANC (p =0,015) service, there was relation between self-practice midwife on contraception service (p =0,003), there was relation between self-practice midwife on maternity (p =0,006). There were relations among self-practice midwife with Antenatal Care, contraception method, and maternity services on Covid-19 pandemic period in Palu city